A Collaborative Writing Tool on Cloud Environment (International Journal of Engineering and Computer Science, 2013)
: Collaborative writing describes a full length writing assignment completed in pairs or small groups. Collaborative writing (CW)transforms the usually solitary work of writing and editing college papers into a group endeavor. Instructors value such assignmentsbecause of their real world relevance. After all, in most workplaces writing is typically produced by a team or goes through multiple handsfor revising purpose. Even in academia we often collaborate on research and co-author journal articles with the colleagues. Giving studentsthe opportunities to practice writing and editing with others is a prudent step in preparing them for the world after their graduation. Thispaper reports on architecture for supporting collaborative writing that was designed with both pedagogical and software engineeringprinciples in mind, and a first evaluation. The overall aim of this paper is to demonstrate how our system, called iWrite, effectively allowsresearchers and instructors to learn more about the students’ writing activities, particularly about features of individual and group writingactivities that correlate with quality outcomes.